Mechanical and thermal properties of bacterial-cellulose-fibre-reinforced Mater-Bi® bionanocomposite - Nainggolan, Hamonangan; Gea, Saharman; Bilotti, Emiliano; Peijs, Ton; Hutagalung, Sabar D. (Beilstein Journal of Nanotechnology, 2013)
The effects of the addition of fibres of bacterial cellulose (FBC) to commercial starch of Mater-Bi® have been investigated. FBC produced by cultivating Acetobacter xylinum for 21 days in glucose-based medium were purified by sodium hydroxide 2.5 wt % and sodium hypochlorite 2.5 wt % overnight, consecutively. To obtain water-free BC nanofibres, the pellicles were freeze dried at a pressure of 130 mbar at a cooling rate of 10 °C min−1. Both Mater-Bi and FBC were blended by using a mini twin-screw extruder at 160 °C for 10 min at a rotor speed of 50 rpm. Tensile tests were performed according to ASTM D638 to measure the Young’s modulus, tensile strength and elongation at break. A field emission scanning electron microscope was used to observe the morphology at an accelerating voltage of 10 kV. The crystallinity (Tc) and melting temperature (Tm) were measured by DSC. Results showed a significant improvement in mechanical and thermal properties in accordance with the addition of FBC into Mater-Bi. FBC is easily incorporated in Mater-Bi matrix and produces homogeneous Mater-Bi/FBC composite. The crystallinity of the Mater-Bi/FBC composites decrease in relation to the increase in the volume fraction of FBC.
Keywords: bacterial cellulose; bio-nanocomposites; Mater-Bi; mechanical; thermal